Multimodal Facial Aesthetic Treatment on the Appearance of Aging, Social Confidence, and Psychological Well-being: HARMONY Study. (5th March 2021) - Cohen, Joel L; Rivkin, Alexander; Dayan, Steven; Shamban, Ava; Werschler, W Philip; Teller, Craig F; Kaminer, Michael S; Sykes, Jonathan M; Weinkle, Susan H; Garcia, Julie K
Abstract: Background: A global approach to facial rejuvenation involves multiple treatment modalities. Objectives: The aim of this study was to evaluate the impact of multimodal facial aesthetic treatment on self-reported psychological and social outcomes. Methods: HARMONY, a prospective, multicenter, 4-month study, enrolled patients aged 35 to 65 years to receive on-label treatment with a combination of hyaluronic fillers (VYC-20L, HYC-24L, and/or HYC-24L+), onabotulinumtoxinA, and bimatoprost. Fillers were injected on Day 1, with touch-ups performed on Day 14. OnabotulinumtoxinA was injected at Month 3 into glabellar lines and/or crow's feet lines. Patients applied bimatoprost to eyelashes once daily for 17 weeks. Mean change from baseline on FACE-Q Psychological Well-being and Social Confidence Scales, FACE-Q Aging Appearance Appraisal Scale, and FACE-Q Age Appraisal Visual Analog Scale were assessed. Results: Of 100 patients treated, 93 were evaluated at 4 months posttreatment. Significant improvement vs baseline was observed on the FACE-Q Scales for Psychological Well-being (mean change, −19.9; P < 0.00001), Social Confidence (mean change, −18.2; P < 0.00001), and Aging Appearance (mean change, −28.5; P < 0.0001). On average, patients' self-assessed age was 0.1 years older than actual age at baseline and 4.5 years younger at Month 4 ( P < 0.001 vs baseline). Forty-two patients experienced adverse events, all mild to moderate. Conclusions: Multimodal, full facial aesthetic treatment improves patients' self-reported psychological well-being, social confidence, aging appearance, and perceptions of chronologic age. Level of Evidence: 4: